Penurunan Pendapatan Asli Daerah dari Pengujian Laik Jalan Kendaraan Bermotor: Tantangan Tata Kelola Desentralisasi - Hariyati HS; Nur, Muhammad; Rahmat, Muhammad Rais (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The purpose of this study is to analyze the contribution of motor vehicle inspection retribution (PKB) to regional revenue in Sidenreng Rappang Regency and to examine governance-related factors that contribute to the existing problems. The research method employed is a descriptive qualitative approach using an interactive analysis model. The study was conducted at the Motor Vehicle Inspection Unit (UPT Pengujian Kendaraan Bermotor) during the period from November 2024 to January 2025. Data collection involved in-depth interviews, direct observation, and document analysis.The findings indicate that since 2019 there has been a significant decline in the realization of retribution revenue, with achievement reaching only 51.73% in 2023 substantially lower than the achievement rate of over 95% during the 2014–2018 period. The main factors contributing to this decline include low public compliance, weak enforcement of sanctions, poor service quality, limited infrastructure, and a low level of public trust in the managing institution. In addition, weaknesses were identified in the monitoring and evaluation system, as well as outdated operational procedures. This study recommends regulatory reform, digitalization of KIR testing and retribution payment processes, community-based public education campaigns, and the strengthening of ethical and accountable leadership to improve governance, enhance public services, and promote regional fiscal independence.